The Effect of Nutrition Education Through Domino Obesity and Leaflets on Macronutrient Intake in Obesity Adolescents at SMA Muhammadiyah 1 Palemban - Hana Wulandari; Podojoyo Podojoyo; Yuli Hartati (Journal of Innovative and Creativity (Joecy), 2026)
Obesity is a global health problem and continues to increase every year, which has an impact on increasing the risk of morbidity and death. In responding to the obesity rate, interventions that are nutritional education are needed. As nutrition education technology develops, obesity domino print media and leaflets are effective media to assist the learning process. The aim of this research was to determine the effect of nutrition education through obesity domino print media and leaflets on macronutrient intake in obese adolescents at SMA Muhammadiyah 1 Palembang. This quasi-experimental research with a pre and posttest control group design aims to determine the influence of nutrition education through obesity domino print media and leaflets on obesity macronutrient intake at SMA Muhammadiyah 1 Palembang. The number of respondents in the treatment and comparison groups was 35 respondents each. In the treatment group, nutritional education was provided through obesity dominoes and in the comparison group, printed leaflets. The statistical test results in the independent t-test showed that the p-value for energy intake was 0.035 (p-value<0.05), protein intake 0.475 (p-value>0.05), fat intake 0.515 (p-value>0.05), and carbohydrate intake 0.000 (p-value <0.05). Nutrition education through video media and leaflets showed the energy intake and carbohydrate intake of respondents but there was no effect on the protein intake and fat intake of obese respondents at SMA Muhammadiyah 1 Palembang